O ensino de língua inglesa para crianças por meio da internet - Marini, Edna dos Santos (2010)
This study aims to observe whether the use of the Internet in English language lessons positively affects learning, participation and engagement, by comparing a teaching-learning English language mediated through the internet with a situation mediated by analog materials (magazines, flashcards, books). Based on the analysis into two classes, in a private school and in a public school, I conduct a discussion about using the Internet or not, English classes for children from lower grades of elementary school. To develop this work, we base Vygotskian theoretical research by considering the interaction, learning and the zone of proximal development. We followed a report on the communicative approach, learning through the Internet and the process of foreign language education for children (LEC). The analysis and discussion of the results show that both, the use of the Internet as the classroom through authentic materials analogue facilitate motivation, engagement and learning, provided there is a mediation of the teacher